2021
DOI: 10.1155/2021/6664627
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Wound Healing Potential of Photobiomodulation Is Possibly Mediated by Its Stimulatory Effect on AKT Expression in Adipose‐Derived Stem Cells

Abstract: Increasing evidence suggests that adipose-derived stem cells (ADSCs) serve as a therapeutic approach for wound healing. The aim of this study was to determine the effect of photobiomodulation (PBM) on antioxidant enzymes in ADSCs. Four ADSC cell models, namely, normal, wounded, diabetic, and diabetic wounded, were irradiated with 660 nm (fluence of 5 J/cm2 and power density of 11.2 mW/cm2) or 830 nm (fluence of 5 J/cm2 and power density of 10.3 mW/cm2). Nonirradiated cells served as controls. Cell morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…An increasing body of evidence supports the role of PBM in promoting wound healing by activating the AKT signaling pathway, which assists in elevating antioxidant levels. 38 PBM has also been found to inhibit the FOXO1 signaling pathway, thereby reducing oxidative stress biomarkers in diabetic wound fibroblasts. 39 Moreover, a previous study reported that diabetic hypoxic wound models reacted positively to PBM.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence supports the role of PBM in promoting wound healing by activating the AKT signaling pathway, which assists in elevating antioxidant levels. 38 PBM has also been found to inhibit the FOXO1 signaling pathway, thereby reducing oxidative stress biomarkers in diabetic wound fibroblasts. 39 Moreover, a previous study reported that diabetic hypoxic wound models reacted positively to PBM.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidative stress [ 93 ] and anti-apoptotic [ 94 ] effects of substances secreted by ADSCs are critical for repairing radiation-induced DNA damage in the acute phase and preventing the exacerbation of damage caused by the bystander effect. ADSC can effectively activate the antioxidant system, such as superoxide dismutase (SOD) [ 95 , 96 ], Nrf2-antioxidant response element (ARE) pathway [ 97 99 ] and so on.…”
Section: The Therapeutic Value Of Adipose-derived Stem Cells (Adscs) ...mentioning
confidence: 99%
“…Feng et al (2020) [50] suggested that PBM (808 nm; 1 J/cm 2 and 2 J/cm 2 ) enhances wound healing by promoting the migration of gingival stem cells via the ROS/JNK/NF-κB/MMP-1 signalling pathway. Rajendran et al (2021) [51] noticed decreased oxidative stress through the activation of forkhead Box O1 (FOXO1) in adipose stem cells when PBM (660 nm; 5 J/cm 2 ) was used. Rhee et al (2019) [52] observed reduced neuronal cell polarity and increased cell proliferation, viability and activation of Src, Ras, and MAPK signalling when PBM (660 nm; 0.78, 1.56, 3.12, 6.24, 9.36 J/cm 2 ) was used.…”
Section: Photobiomodulation (Pbm) and The Activation Of Signalling Pa...mentioning
confidence: 99%